Development of antihunt systems of sauces in the technology of fish products - Никитчина, Татьяна Ивановна; Маноли, Татьяна Анатольевна; Барышева, Яна Олеговна (Eastern-European Journal of Enterprise Technologies, 2015)
Despite the well-known research and application of plant and microbial polysaccharides in food technology, including canned fish technology as thickeners and jelling agents for various fillings, there is a certain deficiency in this assortment, caused by the complexity of technological processes that would allow to obtain high-quality finished products. It was found that low-esterified pectin substances of plant raw materials, obtained by biotechnological method allow to make structured products, expanding the assortment of fish products with improved organoleptic and functional properties. A comprehensive evaluation of the properties of pectin substances and pectinmethylesterases used for jellied vegetable sauces in the manufacture of fish products was performed in the paper. The optimal conditions for the biotechnological sauce jellification method were obtained, and organoleptic characteristics of canned fish in the jelling sauce were investigated. The results of organoleptic evaluation showed that the analyzed canned products had identical high points on almost all counts. All samples had a pleasant taste and flavour, delicate texture of fish meat in a uniform structured sauce.